Asymmetry of marine invasions across tropical oceans. Issue 8 (14th July 2021) - Torchin, Mark E.; Freestone, Amy L.; McCann, Linda; Larson, Kristen; SchlÖder, Carmen; Steves, Brian P.; Fofonoff, Paul; Repetto, Michele F.; Ruiz, Gregory M.
Abstract: Understanding the mechanisms of spatial variation of biological invasions, across local‐to‐global scales, has been a major challenge. The importance of evolutionary history for invasion dynamics was noted by Darwin, and several studies have since considered how biodiversity of source and recipient regions can influence the probability of invasions. For over a century, the Panama Canal has connected water bodies and biotas with different evolutionary histories, and created a global shipping hot spot, providing unique opportunities to test mechanisms that affect invasion patterns. Here, we test for asymmetry in both the extent of invasions and predation effects, a possible mechanism of biotic resistance, between two tropical oceans at similar latitudes. We estimated nonnative species (NNS) richness for sessile marine invertebrates, using standardized field surveys and literature synthesis, to examine whether invasions are asymmetrical, with more NNS present in the less diverse Pacific compared to the Atlantic. We also experimentally tested whether predation differentially limits the abundance and distribution of these invertebrates between oceans. In standardized surveys, observed total NNS richness was higher in the Pacific (18 NNS, 30% of all Pacific species) than the Atlantic (11 NNS, 13% of all Atlantic species). Similarly, literature‐based records also display this asymmetry between coasts. When considering only the reciprocal exchange of NNS between Atlantic and Pacific biotas, NNS exchange from Atlantic to Pacific was eightfold higher than the opposite direction, exceeding the asymmetry predicted by random exchange based simply on differences of overall diversity per region. Predation substantially reduced biomass and changed NNS composition in the Pacific, but no such effects were detected on the Atlantic coast. Specifically, some dominant NNS were particularly susceptible to predation in the Pacific, supporting the hypothesis that predation may reduce the abundance of certain NNS here. These results are consistent with predictions that high diversity in source regions, and species interactions in recipient regions, shape marine invasion patterns. Our comparisons and experiments across two tropical ocean basins, suggest that global invasion dynamics are likely driven by both ecological and evolutionary factors that shape susceptibility to and directionality of invasions across biogeographic scales.